Study of a low alloy steel rust using Mössbauer spectroscopy. - Maier, I. A.; Saragovi-Badler, C.; Labenski, F. (Academia de Ciencias de Hungría, 1978)
Fil: Maier, I. A. Comisión Nacional de Energía Atómica; Argentina